Positive electrode, all-solid-state lithium battery

By introducing organic substances containing thiol and carboxyl groups as additives into the positive electrode coating of an all-solid lithium battery, the chemical connection between the positive electrode active material particles and the sulfur-based electrolyte particles is achieved, and the cycle performance problem caused by poor contact is solved, and the cycle performance of the battery is significantly improved.

CN113851650BActive Publication Date: 2025-03-07BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010601546.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-28
Publication Date
2025-03-07
Estimated Expiration
2040-06-28

AI Technical Summary

Technical Problem

The poor contact between the positive electrode particles and the electrolyte particles in the positive electrode coating of an all-solid lithium battery leads to poor circulation performance, and the physical pressurization method fails during the circulation, resulting in a sharp reduction in battery performance.

Method used

The positive electrode coating is introduced as additives, and the positive electrode active material particles are connected to the sulfur-based electrolyte particles through chemical action to improve the contact tightness between them.

Benefits of technology

The contact force between the positive electrode particles and the electrolyte particles is improved through chemical connections, reducing the problem of contact deterioration caused by volume expansion during the cycle, and significantly improving the circulation performance of all-solid lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113851650B_ABST
    Figure CN113851650B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium-ion batteries, and specifically to a positive electrode sheet and an all-solid-state lithium battery. The positive electrode sheet includes a current collector and a positive electrode coating on its surface, and the positive electrode coating includes: a positive electrode active material, a sulfur-based electrolyte and an additive, wherein the additive includes an organic substance containing a thiol group and a carboxyl group, and the number of main chain carbon atoms in the organic substance is selected from an integer of 1-5. The present invention adds an additive to the positive electrode coating, which increases the contact tightness between the positive electrode active material particles and the sulfur-based electrolyte particles, which is beneficial to charge transfer; at the same time, the additive also effectively avoids the situation where the contact is deteriorated due to the change in battery cycle volume, greatly improving the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a positive electrode sheet and an all-solid-state lithium battery. Background Art

[0002] In the positive electrode coating of all-solid-state lithium batteries, the contact between the positive electrode particles and the electrolyte particles is solid-solid physical contact, and the contact condition significantly affects the performance of solid-state batteries. At present, the main means to improve the contact condition is to apply external pressure to the composite positive electrode layer, such as hot pressing, rolling, etc.

[0003] Although the method of increasing the contact between the positive electrode particles and the electrolyte particles by physical pressure can increase the capacity of the battery, especially in the early stage of the cycle, to a certain extent, it aggravates the side reactions between the positive electrode particles and the electrolyte particles, resulting in increased interface impedance and poor contact, which reduces the cycle performance of the all-solid-state lithium battery. In addition, the volume expansion during the battery cycle also makes the physical contact ineffective, thereby sharply reducing the cycle performance of the all-solid-state lithium battery. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of poor cycle performance in the positive electrode coating of the prior art all-solid-state lithium battery due to poor contact between the positive electrode particles and the electrolyte particles, and to provide a positive electrode sheet and an all-solid-state lithium battery. The positive electrode sheet can effectively avoid the problem of poor cycle performance of the all-solid-state lithium battery and improve the cycle performance of the battery.

[0005] In order to achieve the above object, the present invention provides a positive electrode sheet in a first aspect, the positive electrode sheet comprises a current collector and a positive electrode coating on the surface thereof, the positive electrode coating comprises: a positive electrode active material, a sulfur-based electrolyte and an additive,

[0006] Wherein, the additive is an organic substance containing a thiol group and a carboxyl group, and the number of carbon atoms in the main chain of the organic substance is selected from an integer of 1-5.

[0007] Preferably, the number of thiol groups in the additive is 1-2, and the number of carboxyl groups in the additive is 1-2.

[0008] Preferably, the content of the additive in the positive electrode coating is 0.1-5% by weight.

[0009] A second aspect of the present invention provides an all-solid-state lithium battery, which includes the above-mentioned positive electrode sheet, negative electrode sheet and electrolyte layer.

[0010] Compared with the prior art, the technical solution provided by the present invention, by introducing additives, transforms the contact between the positive electrode active material particles and the sulfur-based electrolyte particles in the positive electrode coating from a physical effect (physical contact between particles) to a chemical effect (particles are connected through the functional groups of the additives), thereby increasing the closeness of the contact between the two, which is beneficial to charge transfer, thereby reducing the problem of poor contact caused by volume expansion of the positive electrode active material particles during the cycle of the positive electrode coating, thereby greatly improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a test curve diagram of specific capacity-cycle number of all-solid-state lithium batteries prepared in Example 1 and Comparative Example 1;

[0012] FIG2( a ) is a SEM image of the positive electrode sheet in the all-solid-state lithium battery of Example 1 after 100 cycles;

[0013] FIG2( b ) is a SEM image of the positive electrode sheet in the all-solid-state lithium battery of Example 1 after 100 cycles. DETAILED DESCRIPTION

[0014] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0015] The first aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprises a current collector and a positive electrode coating on the surface thereof, the positive electrode coating comprises: a positive electrode active material, a sulfur-based electrolyte and an additive,

[0016] Wherein, the additive is an organic substance containing a thiol group and a carboxyl group, and the number of carbon atoms in the main chain of the organic substance is selected from an integer of 1-5.

[0017] The inventor of the present invention has found through research that in the prior art, the physical contact between the positive electrode active material particles and the sulfur-based electrolyte particles is increased by physical pressurization to improve the battery cycle performance. However, this physical contact will fail as the volume of the positive electrode coating expands during battery cycling, thereby causing the battery cycle performance to deteriorate. The present invention introduces an additive into the positive electrode coating to effectively improve the contact between the positive electrode active material particles and the sulfur-based electrolyte particles through chemical action, thereby greatly increasing the interaction between the two. The additive has a shorter molecular chain that is beneficial to the transmission of charge, thereby improving the battery cycle performance.

[0018] Specifically, the carboxyl functional group in the additive is linked to the positive electrode active material particles by acid-base neutralization reaction with the hydroxyl group (-OH) remaining on the surface of the positive electrode active material particles; the thiol functional group is linked to the positive electrode active material particles by S atoms and the exposed cations (Li + , P5+ ,Ge 4+ Compared with physical contact, the present invention introduces organic matter containing carboxyl functional groups and thiol functional groups, and the number of main chain carbon atoms in the organic matter is selected from an integer of 1-5 (additive), and connects the positive electrode active material particles and the sulfur-based electrolyte particles through chemical action, which effectively increases the interaction between the two, avoids the situation where the contact between the positive electrode active material particles and the sulfur-based electrolyte particles deteriorates due to volume expansion during the cycle, and thus improves the cycle performance of the all-solid-state lithium battery.

[0019] In the present invention, there is a wide range of choices for the types of the additives. Preferably, the additive is selected from at least one of alkanes, alkenes and alkynes containing thiol and carboxyl groups, preferably alkanes containing thiol and carboxyl groups.

[0020] Preferably, the thiol group in the additive is a terminal functional group and / or a branched functional group, and the carboxyl group is a terminal functional group and / or a branched functional group; further preferably, the thiol group and the carboxyl group in the additive are both terminal functional groups. The use of the preferred conditions is conducive to the additive effectively linking the positive electrode active material particles and the sulfur-based electrolyte particles, while also ensuring the charge transfer between the two.

[0021] Preferably, the number of thiol groups in the additive is 1-2, and the number of carboxyl groups in the additive is 1-2; further preferably, the number of thiol groups and carboxyl groups in the additive is both 1.

[0022] In the present invention, preferably, the additive is selected from at least one of thioglycolic acid, mercaptopropionic acid, 5-mercaptovaleric acid, 3-mercaptovaleric acid, 3-mercapto-1,5-pentanedioic acid, 3,5-dimercaptovaleric acid, 2-methylmercaptobutyric acid, 2-mercaptopropionic acid and mercaptodipropionic acid, and is further preferably selected from thioglycolic acid and / or mercaptopropionic acid.

[0023] In the present invention, the positive electrode active material has a wide selection range. Preferably, the positive electrode active material is selected from at least one of lithium cobalt oxide material, lithium manganese oxide material, nickel cobalt manganese material and nickel cobalt aluminum material; further preferably, the particle size of the positive electrode active material is 3-15 μm.

[0024] According to the present invention, preferably, the sulfur-based electrolyte is a sulfur-based solid electrolyte, and the sulfur-based solid electrolyte is selected from a sulfur-based crystalline electrolyte and / or a sulfur-based glassy electrolyte; further preferably, the particle size of the sulfur-based electrolyte is 1-5 μm.

[0025] Preferably, the molecular formula of the sulfur-based solid electrolyte is Li x M y P z Sw , where M is selected from at least one of Si, Ge and Sn, x+4y+5z=2w, 1≤x≤10, 0≤y≤1.5, 1≤z≤5, 3≤w≤20, for example: Li 10 GeP2S 12 ; The sulfur-based crystalline electrolyte is selected from Li7P3S 11 and / or 70Li2S-30P2S5; the sulfur-based glassy electrolyte is selected from Li3PS4 and / or Li7P3S 11 .

[0026] According to a preferred embodiment of the present invention, the content of the additive in the positive electrode coating is 0.1-5% by weight. The preferred conditions are beneficial to increase the contact tightness between the positive electrode active material particles and the sulfur electrolyte particles, which is beneficial to charge transfer; at the same time, the additive also effectively avoids the situation where the contact is deteriorated due to the change in battery cycle volume, greatly improving the cycle performance of the battery.

[0027] According to the present invention, preferably, the positive electrode coating further includes a conductive agent and / or a binder.

[0028] Preferably, the conductive agent is selected from at least one of graphite, carbon black, acetylene black and graphene; the binder is selected from fluorine-containing resins and / or polyolefins, and is further preferably selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex.

[0029] According to the present invention, preferably, the weight ratio of the positive electrode active material, sulfur electrolyte, conductive agent, binder and additive is 60-95: 5-50: 0-20: 0-20: 0.1-5, preferably 60-95: 5-50: 1-20: 1-20: 0.1-5, and further preferably 75-85: 20-30: 2-5: 2-5: 0.5-1. The preferred weight ratio is more conducive to improving the construction of electron channels and ion channels in the positive electrode coating.

[0030] The method for preparing the positive electrode sheet comprises the following steps:

[0031] (1) mixing a positive electrode active material, a sulfur-based electrolyte, an additive and an organic solvent to obtain a positive electrode slurry;

[0032] (2) coating the positive electrode slurry on a current collector, and then drying and rolling to obtain a positive electrode sheet;

[0033] Wherein, the additive is an organic substance containing a thiol group and a carboxyl group, and the number of carbon atoms in the main chain of the organic substance is selected from an integer of 1-5.

[0034] In the present invention, unless otherwise specified, the method for preparing the positive electrode sheet is carried out in an inert atmosphere, wherein the inert atmosphere is provided by an inert gas, and the inert gas is selected from at least one of nitrogen, helium, argon and neon, preferably nitrogen.

[0035] According to the present invention, preferably, the step (1) further comprises a conductive agent and / or a binder.

[0036] In the present invention, there is no particular limitation on the mixing method in step (1), as long as the positive electrode active material, sulfur-based electrolyte, conductive agent, binder, additive and organic solvent are uniformly mixed. Preferably, the mixing includes: A. first mixing the binder, additive and organic solvent to obtain a first mixed slurry; B. second mixing the first mixed slurry with the sulfur-based electrolyte to obtain a second mixed slurry; C. adding a pH regulator to the second mixed slurry to adjust the pH to 8-11, and then adding the positive electrode active material and conductive agent for third mixing to obtain a positive electrode slurry. The preferred mixing conditions are more conducive to more uniform mixing of different particles, and a reasonable mixing order is conducive to better exerting the linking effect of the binder.

[0037] In the present invention, unless otherwise specified, the first mixing, the second mixing and the third mixing are all conventional technical means in the art, and the present invention will not elaborate on them herein.

[0038] In the present invention, the organic solvent has a wide selection range, as long as the positive electrode active material, sulfur electrolyte, conductive agent, binder, and additive are uniformly dissolved. Preferably, the organic solvent is selected from at least one of nitrogen methyl pyrrolidone, toluene, xylene, and n-heptane.

[0039] In the present invention, the types and weight ratios of the positive electrode active material, sulfur-based electrolyte, conductive agent, binder, and additives in step (1) are in accordance with the above-mentioned definitions, and the present invention will not elaborate on this.

[0040] In the present invention, the pH regulator is selected from at least one of ammonia water, lithium hydroxide and lithium oxide. The pH of the second mixed slurry is adjusted to 8-11 by using the pH regulator to provide an alkaline environment so that more -COO - The groups are exposed to the outside so as to provide more effective groups for subsequent reactions with the surface of the positive electrode active material particles.

[0041] According to the present invention, preferably, the drying conditions include: a temperature of 60-150° C., preferably 80-120° C., and a time of 5-20 hours, preferably 8-15 hours. In the embodiment of the present invention, the drying is performed in an oven, but the present invention is not limited thereto.

[0042] Preferably, the rolling conditions include: a pressure of 0.1-20 MPa, preferably 0.5-15 MPa, a rotation speed of 0.1-20 rpm, preferably 0.1-10 rpm, and further preferably, the rolling is performed in a rolling machine, but the present invention is not limited thereto.

[0043] According to a preferred embodiment of the present invention, the positive electrode slurry prepared in step (1) is coated on an aluminum foil current collector by coating, placed in an oven at 60-150° C. to dry for 5-20 hours, and then rolled in a rolling machine to obtain a positive electrode sheet, wherein the rolling pressure is 0.1-20 MPa and the rolling speed is 0.1-20 rpm.

[0044] A second aspect of the present invention provides an all-solid-state lithium battery, which includes the above-mentioned positive electrode sheet, negative electrode sheet and electrolyte layer.

[0045] According to the present invention, preferably, the thickness ratio of the positive electrode sheet, the negative electrode sheet and the electrolyte layer is 20-50:10-30:20-40, preferably 35-45:20-30:30-40. The preferred thickness ratio is conducive to the effective transmission of charge and improves the theoretical capacity of the all-solid-state lithium battery; wherein the thickness is measured by the screw micrometer method. Further preferably, the material of the electrolyte layer is a sulfur-based electrolyte.

[0046] In the present invention, unless otherwise specified, the thickness of the negative electrode sheet and the positive electrode sheet do not include the thickness of the current collector, that is, the thickness of the negative electrode sheet refers to the thickness of the negative electrode coating (negative electrode slurry), and the thickness of the positive electrode sheet refers to the thickness of the positive electrode coating (positive electrode slurry).

[0047] According to a preferred embodiment of the present invention, the preparation method of the electrolyte layer comprises: mixing a sulfur-based electrolyte and a binder in an organic solvent at a weight ratio of 90-99.9:0.1-10 to obtain an electrolyte slurry, and then uniformly coating the electrolyte slurry on the above-mentioned positive electrode sheet, and then drying and rolling to obtain an electrolyte layer coated on the positive electrode sheet.

[0048] According to the present invention, preferably, the negative electrode sheet comprises a negative electrode active material capable of lithium insertion and removal and a binder, wherein the negative electrode active material capable of lithium insertion and removal refers to a material that can be used as a negative electrode and has a relatively low potential and can be used for lithium ion insertion and removal; further preferably, the negative electrode active material is selected from at least one of graphite, acetylene black, graphene, activated carbon, metallic lithium, lithium-indium alloy and silicon.

[0049] According to a preferred embodiment of the present invention, the preparation method of the negative electrode sheet comprises: mixing the negative electrode active material and the binder in deionized water at a weight ratio of 90-99.9:0.1-10 to obtain a negative electrode slurry, and then uniformly coating the negative electrode slurry on a copper foil current collector, and then drying and rolling to obtain a negative electrode sheet.

[0050] In the present invention, there is no particular limitation on the preparation method of the all-solid-state lithium battery, as long as the positive electrode sheet, the electrolyte layer and the negative electrode sheet are subjected to rolling treatment. Preferably, the conditions of the rolling treatment include: a pressure of 0.1-20MPa, preferably 0.5-15MPa, and a rotation speed of 0.1-20rpm, preferably 0.1-10rpm.

[0051] The present invention will be described below by way of examples.

[0052] The dimensions of the aluminum foil include: a width of 160 mm and a thickness of 16 μm; the dimensions of the copper foil include: a width of 160 mm and a thickness of 16 mm.

[0053] Examples 1-9 and Comparative Examples 1-3 were all carried out in an inert atmosphere of a glove box.

[0054] Example 1

[0055] (1) Preparation of positive electrode 1) A. 15 g polyvinylidene fluoride (PVDF), 1 g thioglycolic acid and 500 mL nitrogen methyl pyrrolidone (NMP) were first mixed to obtain a first mixed slurry; B. The first mixed slurry was mixed with 80 g Li 10 GeP2S 12 Carry out a second mixing, then add ammonia water to adjust the pH to 9 to obtain a second mixed slurry; C. Carry out a third mixing of the second mixed slurry with 100g of lithium cobalt oxide and 10g of graphite to obtain a positive electrode slurry; 2) Evenly coat the positive electrode slurry on an aluminum foil, then dry at 100°C for 12h, and roll to obtain a positive electrode sheet S1, wherein the rolling pressure is 0.5MPa and the rolling speed is 1rpm.

[0056] (2) Preparation of electrolyte layer : 500g Li 10 GeP2S 12, 20 g PVDF and 1000 mL toluene are mixed to obtain an electrolyte slurry; the electrolyte slurry is evenly coated on the above-mentioned positive electrode sheet S1, and then dried at 100° C. for 12 h, rolled and cut to obtain an electrolyte layer and a positive electrode sheet of 50 mm×200 mm, wherein the rolling pressure is 0.5 MPa and the rolling speed is 1 rpm.

[0057] (3) Preparation of negative electrode : 500 g of graphite, 20 g of sodium carboxymethyl cellulose (CMC), 10 g of styrene-butadiene rubber (SBR) and 1000 mL of deionized water were mixed to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on a copper foil, and then dried at 100° C. for 12 h, rolled and cut to obtain a 50 mm×200 mm negative electrode sheet, wherein the rolling pressure was 0.5 MPa and the rolling speed was 1 rpm.

[0058] (4) Assembly of all-solid-state lithium batteries : The electrolyte layer and the positive electrode sheet obtained in step (2) are aligned, rolled, and cut with the negative electrode sheet obtained in step (3) to obtain a disc with a diameter of 15 mm, which is encapsulated in a button battery shell to obtain an all-solid-state lithium battery SP-1, wherein the rolling pressure is 3 MPa and the rolling speed is 1 rpm.

[0059] Example 2

[0060] (1) Preparation of positive electrode : 1) A. 5 g of polytetrafluoroethylene (PTFE), 0.1 g of mercaptopropionic acid and 500 mL of nitrogen methyl pyrrolidone (NMP) were first mixed to obtain a first mixed slurry; B. The first mixed slurry was mixed with 30 g of Li7P3S 11 Carry out a second mixing, then add ammonia water to adjust the pH to 8 to obtain a second mixed slurry; C. Carry out a third mixing of the second mixed slurry with 100g of lithium cobalt oxide and 10g of acetylene black to obtain a positive electrode slurry; 2) Evenly coat the positive electrode slurry on an aluminum foil, then dry at 120°C for 10h, and roll to obtain a positive electrode sheet S2, wherein the rolling pressure is 0.1MPa and the rolling speed is 5rpm.

[0061] (2) Preparation of electrolyte layer : 500g Li7P3S 11 , 20 g PVDF and 1000 mL toluene are mixed to obtain an electrolyte slurry; the electrolyte slurry is evenly coated on the above-mentioned positive electrode sheet S2, and then dried at 100° C. for 12 h, rolled and cut to obtain an electrolyte layer and a positive electrode sheet of 50 mm×200 mm, wherein the rolling pressure is 0.1 MPa and the rolling speed is 5 rpm.

[0062] (3) Preparation of negative electrode: 500g activated carbon, 10g SBR and 1000mL deionized water were mixed to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on a copper foil, and then dried at 100°C for 12h, rolled and cut to obtain a 50mm×200mm negative electrode sheet, wherein the rolling pressure was 0.1MPa and the rolling speed was 5rpm.

[0063] (4) Assembly of all-solid-state lithium batteries : The electrolyte layer and positive electrode sheet obtained in step (2) are aligned, rolled and cut with the negative electrode sheet obtained in step (3) to obtain a disc with a diameter of 15 mm, which is encapsulated in a button battery shell to obtain an all-solid-state lithium battery SP-2.

[0064] Example 3

[0065] (1) Preparation of positive electrode 1) A. 20 g of acrylic resin, 2 g of mercaptobutyric acid and 500 mL of nitrogen methyl pyrrolidone (NMP) were first mixed to obtain a first mixed slurry; B. The first mixed slurry was mixed with 10 g of Li7P3S 11 Carry out a second mixing, then add ammonia water to adjust the pH to 11 to obtain a second mixed slurry; C. Carry out a third mixing of the second mixed slurry with 100g of lithium cobalt oxide and 10g of carbon black to obtain a positive electrode slurry; 2) Evenly coat the positive electrode slurry on an aluminum foil, then dry at 120°C for 10h, and roll to obtain a positive electrode sheet S3, wherein the rolling pressure is 15MPa and the rolling speed is 3rpm.

[0066] (2) Preparation of electrolyte layer : 500g Li 10 GeP2S 12 , 20g of acrylic resin and 1000mL of toluene are mixed to obtain an electrolyte slurry; the electrolyte slurry is evenly coated on the above-mentioned positive electrode sheet S3, and then dried at 100°C for 12h, rolled and cut to obtain an electrolyte layer and a positive electrode sheet of 50mm×200mm, wherein the rolling pressure is 15MPa and the rolling speed is 3rpm.

[0067] (3) Preparation of negative electrode : 500g activated carbon, 10g SBR and 1000mL deionized water were mixed to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on a copper foil, and then dried at 80°C for 15h, rolled and cut to obtain a 50mm×200mm negative electrode sheet, wherein the rolling pressure was 15MPa and the rolling speed was 3rpm.

[0068] (4) Assembly of all-solid-state lithium batteries : The electrolyte layer and positive electrode sheet obtained in step (2) are aligned, rolled and cut with the negative electrode sheet obtained in step (3) to obtain a disc with a diameter of 15 mm, which is encapsulated in a button battery shell to obtain an all-solid-state lithium battery SP-3.

[0069] Example 4

[0070] The positive electrode sheet was prepared according to Example 1, except that the mass of thioglycolic acid was replaced with 2 g, to obtain a positive electrode sheet S4;

[0071] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery SP-4.

[0072] Example 5

[0073] The positive electrode sheet was prepared according to Example 1, except that the thioglycolic acid was replaced with an equal mass of mercaptovaleric acid to obtain a positive electrode sheet S5;

[0074] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery SP-5.

[0075] Example 6

[0076] The positive electrode sheet was prepared according to Example 1, except that the thioglycolic acid was replaced with an equal mass of 3-mercaptovaleric acid to obtain a positive electrode sheet S6;

[0077] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery SP-6.

[0078] Example 7

[0079] The positive electrode sheet was prepared according to Example 1, except that the thioglycolic acid was replaced with an equal mass of 3-mercapto-1,5-pentanedioic acid to obtain a positive electrode sheet S7;

[0080] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery SP-7.

[0081] Example 8

[0082] The positive electrode sheet was prepared according to Example 1, except that the thioglycolic acid was replaced with an equal mass of 3,5-dimercaptopentanoic acid to obtain a positive electrode sheet S8;

[0083] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery SP-8.

[0084] Comparative Example 9

[0085] The positive electrode sheet was prepared according to Example 1, except that the mass of thioglycolic acid was replaced with 5 g, to obtain a positive electrode sheet S9;

[0086] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery SP-9.

[0087] Comparative Example 1

[0088] The positive electrode sheet was prepared according to Example 1, except that thioglycolic acid was replaced with acetic acid of equal mass, to obtain a positive electrode sheet D1;

[0089] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery DP-1.

[0090] Comparative Example 2

[0091] The positive electrode sheet was prepared according to Example 1, except that thioglycolic acid was replaced with ethyl mercaptan of equal mass, to obtain a positive electrode sheet D2;

[0092] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery DP-2.

[0093] Comparative Example 3

[0094] The positive electrode sheet D3 was obtained by preparing the positive electrode sheet in Example 1 except that no additive was added, that is, 1 g of thioglycolic acid was not added;

[0095] The remaining steps are the same as those in Example 1 to obtain an all-solid-state lithium battery DP-3.

[0096] Table 1

[0097]

[0098] Note: * refers to the mass percentage of additives / (positive electrode active material + sulfur electrolyte + conductive agent + binder + additives).

[0099] Test Example 1

[0100] The all-solid-state lithium batteries prepared in Examples 1-9 and Comparative Examples 1-3 were subjected to charge and discharge cycle tests.

[0101] Test conditions: 20 all-solid-state lithium batteries (SP-1 to SP-9 and DP-1 to DP-3); test equipment: LAND CT2001C secondary battery performance test device; test temperature: room temperature (25°C), charge and discharge cycle test at 0.1C.

[0102] Test procedure: let stand for 10 minutes; charge at constant voltage until 4.3V and stop; let stand for 10 minutes; discharge at constant current until 3V, which is one cycle. Repeat this step, and when the number of cycles reaches 100, the cycle ends. The average test results are listed in Table 2.

[0103] in,

[0104] The specific capacity-cycle number test curves of the all-solid-state lithium battery prepared in Example 1 and Comparative Example 1 are as follows: Figure 1 shown.

[0105] Depend on Figure 1 It can be seen that after 100 cycles, the remaining capacity of Example 1 is 81.3%, and that of Comparative Example 1 is 51.1%, indicating that the cycle performance of Example 1 is better than that of Comparative Example 1. Therefore, the all-solid-state lithium battery provided by the present invention effectively improves the cycle performance of the battery.

[0106] Table 2

[0107]

[0108] It can be seen from the data in Table 1-2 that, compared with Comparative Examples 1-3, using the positive electrode sheet containing additives provided by the present invention in an all-solid-state lithium battery can effectively improve the cycle performance of the battery.

[0109] Test Example 2

[0110] The positive electrode sheets of the batteries of Example 1 and Comparative Example 1 after 100 cycles were subjected to SEM scanning test.

[0111] Test method: After 100 cycles, the all-solid-state lithium batteries SP-1 and DP-1 were disassembled in an inert atmosphere, the positive electrode sheets were separated, and the positive electrode sheets were transferred to the electron microscope sample chamber in a vacuum transfer box to isolate the air. The cross-sectional morphology was observed. The test results are shown in Figure 2(a) and Figure 2(b), respectively.

[0112] After 100 cycles, the solid particles of the positive electrode sheet in Example 1 (Figure 2 (a)) remain in a relatively tight state, while in Comparative Example 1 (Figure 2 (b)), obvious gaps appear in the positive electrode sheet, and the contact between the particles is much looser, which is why the battery cycle volume change leads to a significant deterioration in performance. This shows that the introduction of the additive of the present invention has played a role in compacting the contact between the particles, effectively reducing the impact of the volume change during the cycle process, and greatly improving the cycle performance of the battery.

[0113] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any suitable manner. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode sheet, comprising a current collector and a positive electrode coating on its surface, characterized in that: The positive electrode coating comprises: a positive electrode active material, a sulfur-based electrolyte and an additive, Wherein, hydroxyl groups remain on the surface of the positive electrode active material particles; The additive comprises an organic substance containing a thiol group and a carboxyl group, and the number of carbon atoms in the main chain of the organic substance is selected from an integer of 1-5; the additive is selected from at least one of thioglycolic acid, mercaptopropionic acid, 5-mercaptovaleric acid, 3-mercaptovaleric acid, 3-mercapto-1,5-pentanedioic acid, 3,5-dimercaptovaleric acid, 2-methylmercaptobutyric acid, 2-mercaptopropionic acid and mercaptodipropionic acid; Wherein, the sulfur-based electrolyte is a sulfur-based solid electrolyte, and the sulfur-based solid electrolyte is selected from a sulfur-based crystalline electrolyte and / or a sulfur-based glassy electrolyte.

2. The positive electrode sheet according to claim 1, characterized in that: The additive is selected from mercaptoacetic acid and / or mercaptopropionic acid.

3. The positive electrode sheet according to claim 1, characterized in that: The content of the additive in the positive electrode coating is 0.1-5% by weight.

4. An all-solid-state lithium battery, characterized in that: The all-solid-state lithium battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte layer; Wherein, the positive electrode sheet is selected from the positive electrode sheet described in any one of claims 1-3.

5. The all-solid-state lithium battery according to claim 4, characterized in that: The thickness ratio of the positive electrode sheet, the negative electrode sheet and the electrolyte layer is 20-50:10-30:20-40.

Citation Information

Patent Citations

  • Solid electrolyte composition, battery electrode sheet and manufacturing method thereof, and all-solid-state secondary battery and manufacturing method thereof

    CN107251308A

  • Material for positive electrodes, electrode sheet for all-solid-state secondary batteries, all-solid-state secondary battery, method for producing electrode sheet for all-solid-state secondary batteries, and method for producing all-solid-state secondary battery

    CN107735887A